How does the Long-Distance Marital Relationships (LDMRs) and Geographically Close Relationships (GCRs) affect Mental Well-being, Physical Health and Communication in Couples? - Misbah Fatimah; Saira Majid Sheikh; Hafsa Mushtaq (Dialogue Social Science Review (DSSR), 2025)
This study aimed to investigate the effects of LDMRs on the mental and physical well-being of couples to examine how these couples deal with their communication gap, family problems, stress, anxiety, depression and any other physical or psychological outcomes. This study looks at and combines the current theoretical and empirical research on the subject at question. It begins by providing an outline of the consequences of LDMRs on the psychological and physical well-being of couples living apart from each other. Second, it determines the literature relies on the empirical as well as theoretical findings found in the literature that has already been published. This advances our knowledge of how LDMRs affect the health and well-being of couples. This study has a significant potential value as it can direct strategies for improving relationships and overall well-being among couples in LDMRs. In addition to healthcare professionals, this may have significant effects on people, families, and communities.